2011
DOI: 10.1103/physrevb.83.064519
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a photoinduced nonthermal superconducting-to-normal-state phase transition in overdoped Bi2Sr2Caet al.

Abstract: Here we report extensive ultrafast time-resolved reflectivity experiments on overdoped Bi2Sr2Ca1−xYxCu2O 8+δ single crystals (TC =78 K) aimed to clarify the nature of the superconducting-to-normal-state photoinduced phase transition. The experimental data show the lack of the quasiparticles decay time divergence at the fluence required to induce this phase transition, in contrast to the thermally-driven phase transition observed at TC and at variance with recently reported photoinduced charge-density-wave and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 51 publications
(187 reference statements)
10
59
1
Order By: Relevance
“…The saturation behavior has been observed in various superconductors and ascribed to the destruction of the superconducting condensate. 6,11,24,25 In the present case, the additional positive component appearing at higher F is attributed to the PG that exhibits higher saturation threshold and therefore becomes dominant after the saturation of the SC component. 6 For the comprehensive assignment of coexisting SC and PG components, we show the T dependence of R/R transients at E pu /E pr = 0.95/1.55 eV with F above the saturation condition in Fig.…”
Section: A Temperature Dependencementioning
confidence: 83%
See 2 more Smart Citations
“…The saturation behavior has been observed in various superconductors and ascribed to the destruction of the superconducting condensate. 6,11,24,25 In the present case, the additional positive component appearing at higher F is attributed to the PG that exhibits higher saturation threshold and therefore becomes dominant after the saturation of the SC component. 6 For the comprehensive assignment of coexisting SC and PG components, we show the T dependence of R/R transients at E pu /E pr = 0.95/1.55 eV with F above the saturation condition in Fig.…”
Section: A Temperature Dependencementioning
confidence: 83%
“…24,25 Our data indicate that there is no abrupt changes in the photoinduced reflectivity during the recovery, which would be an indication of the first-order transition. However, the excitation density is, due to the finite penetration depth, highly inhomogeneous and any abrupt changes could be easily smeared out.…”
Section: Dynamics Of Superconducting Condensate At F F Thmentioning
confidence: 84%
See 1 more Smart Citation
“…Usually the anomalous T dependence of τ exp is observed in many gapped systems, for example, phaseordered systems showing an energy gap opening in the electron band below the transition temperature T c . It has been found that a wide variety of superconductors [1][2][3][4][5][6][7][8][9][10][11][12][13] and density-wave compounds [14][15][16][17][18][19] show diverging behavior of τ exp near T c , as confirmed by femtosecond time-resolved optical spectroscopy. 1,4,5,[7][8][9][10][11][12][13][14][15][16][17]19 The divergence of τ exp in these gapped systems is believed to result from a recursive energy transfer between electrons and phonons.…”
Section: Introductionmentioning
confidence: 90%
“…The saturation behaviour of the transient-reflectivity amplitude with increasing excitation density was observed in a number of gapped systems such as superconductors [8][9][10][11][12][13][14] and charge-density wave compounds 15,16 . The saturation of the transient reflectivity amplitude was associated with a nonthermal destruction of the condensate and complete closure of the gap.…”
Section: A Excitation Density Dependencementioning
confidence: 99%